Emission properties of a plasma cathode based on a glow discharge for generating nanosecond electron beams; Technical Physics; Vol. 44, № 11 - Gushenets V. I.; Koval N. N. Nikolay Nikolaevich; Tolkachev V. S.; Shchanin P. M. (1999, 1999)
Title screen